Stable Ni(II) sites in Prussian blue analogue for selective, ampere-level ethylene glycol electrooxidation - Ji Kai Liu; Mengde Kang; Kai Huang; Hao Guan Xu; Yi Xiao Wu; Xin Yu Zhang; Yan Zhu; Hao Fan; Song Ru Fang; Yi Zhou; Cheng Lian; Peng Fei Liu; et al. (Nature Communications)
Abstract The industrial implementation of coupled electrochemical hydrogen production systems necessitates high power density and high product selectivity for economic viability and safety. However, for organic nucleophiles (e.g., methanol, urea, and amine) electrooxidation in the anode, most catalytic materials undergo unavoidable reconstruction to generate high-valent metal sites under harsh operation conditions, resulting in competition with oxygen evolution reaction. Here, we present unique Ni(II) sites in Prussian blue analogue (NiFe-sc-PBA) that serve as stable, efficient and selective active sites for ethylene glycol (EG) electrooxidation to formic acid, particularly at ampere-level current densities. Our in situ/operando characterizations demonstrate the robustness of Ni(II) sites during EG electrooxidation. Molecular dynamics simulations further illustrate that EG molecule tends to accumulate on the NiFe-sc-PBA surface, preventing hydroxyl-induced reconstruction in alkaline solutions. The stable Ni(II) sites in NiFe-sc-PBA anodes exhibit efficient and selective EG electrooxidation performance in a coupled electrochemical hydrogen production flow cell, producing high-value formic acid compared to traditional alkaline water splitting. The coupled system can continuously operate at stepwise ampere-level current densities (switchable 1.0 or 1.5 A cm−2) for over 500 hours without performance degradation.